Compressive behavior of stretched and composite microlattice metamaterial for energy absorption applications. (1st March 2020) - Osman, Mahmoud M.; Shazly, Mostafa; El-Danaf, Ehab A.; Jamshidi, Parastoo; Attallah, Moataz M.
Abstract: A new proposed truss lattice metamaterial is introduced and compared with the conventional octet truss lattice (OTL) material with regards to specific energy absorption (SEA) and energy absorption efficiency (EAE). The proposed lattice architecture resembles the Face-Centered Cubic (FCC) metamaterial with a mesostructural unit cell with an aspect ratio of 1:1:2, referred to as the stretched cell lattice (SCL). SCL and OTL samples were fabricated from stainless steel 316L by selective laser melting (SLM). Quasi-static compression experiments on the SLM fabricated metamaterials revealed an unstable twisting deformation mode for the SCL, whereas a stable crushing behavior was observed for the OTL. SCL samples provided higher SEA and EAE than OTL by 26% and 17%, respectively. Additionally, it was shown analytically, numerically and experimentally that the yield strength of the proposed SCL is ~80% higher than that of the OTL metamaterials of the same base material and relative density. A hybrid composite lattice structure based on acrylic matrix and the additively manufactured microlattice metamaterials was produced to enhance the struts buckling resistance. The hybrid composite showed a 47% higher specific strength while the SEA and EAE dropped by 31.5% and 30.7%, respectively, when compared to the bare stainless steel microlattice. Dynamic compression experiments using Split Hopkinson Pressure Bar (SHPB) at strain rates in the order of 10 3 /s demonstrated a similar deformation plateau as the static compression experiments with a dynamic increase factor (DIF) of ~1.3 for the bare stainless steel metamaterials and ~2 for the acrylic-stainless steel hybrid composite material.